The Unique Solvability Conditions for a New Class of Absolute Value Equation - Kumar, Shubham; Deepmala, Deepmala (Yugoslav Journal of Operations Research, 2022)
In this article, we investigate the solution of a new class of the absolute value equation (NCAVE) A_1x−|B_1x−c| = d. Based on spectral radius condition, singular value condition and row and column \mathcal{W}-property, some necessary and sufficient conditions for unique solvability for NCAVE are gained. Some new results for the unique solvability of the new generalized absolute value equation (NGAVE) A_1x−|B_1x| = d are also obtained.